2020
DOI: 10.1007/s41030-020-00116-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ambroxol Sustained Release (Mucosolvan® Retard) Compared with Other Formulations in Healthy Volunteers

Abstract: Introduction: Ambroxol is used in the treatment of acute and chronic respiratory conditions characterized by abnormal mucus secretion and impaired mucus transport and is available in a variety of formulations. This study aimed to compare the steady-state (SS) pharmacokinetic characteristics of extended-release (ER) 75-mg retard capsules with two immediaterelease (IR) formulations (60-mg effervescent tablets and 30-mg tablets) over a 24-h period. Methods: An open-label, randomized, three-period, six-sequence cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…From this fact, the released ABX nanoparticles were tested against the lung cancer cells. Additionally, the nanoparticles were found to have higher cancer cells internalization, better cancer cells sensitivity, and higher absorption at the gastric cells, as supported by the literature [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…From this fact, the released ABX nanoparticles were tested against the lung cancer cells. Additionally, the nanoparticles were found to have higher cancer cells internalization, better cancer cells sensitivity, and higher absorption at the gastric cells, as supported by the literature [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionsupporting
confidence: 71%
“…Moreover, ABX was approved for its antioxidant and anti-inflammatory actions when it was studied for treatment of hyperinflammatory diseases, such as psoriasis, and it was also suggested for treating cancer-associated hyperinflammatory status [ 8 ]. Furthermore, intravenous and oral ABX formulations accumulate in the lungs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Ambroxol as a potential pharmacological chaperone therapy in GD ABX is an oral mucolytic drug available over the counter since many years as a cough medicine in various countries with the exception of the United States (Cazan et al, 2018) demonstrated to be highly effective as an expectorant, antiinflammatory, and antioxidant agent due to its extensive history of human use in treating airway mucus hypersecretion diseases such as chronic bronchitis, asthma, and cystic fibrosis (Ollier et al, 2020). Moreover, ABX has been employed as an alternative preventive therapy for hyaline membrane disease in newborns by enhancing the secretion of surfactant in the lungs (Ollier et al, 2020).…”
Section: Current Medicational Options For Gdmentioning
confidence: 99%
“…2 Ambroxol as a potential pharmacological chaperone therapy in GD ABX is an oral mucolytic drug available over the counter since many years as a cough medicine in various countries with the exception of the United States (Cazan et al, 2018) demonstrated to be highly effective as an expectorant, antiinflammatory, and antioxidant agent due to its extensive history of human use in treating airway mucus hypersecretion diseases such as chronic bronchitis, asthma, and cystic fibrosis (Ollier et al, 2020). Moreover, ABX has been employed as an alternative preventive therapy for hyaline membrane disease in newborns by enhancing the secretion of surfactant in the lungs (Ollier et al, 2020). ABX showed an anesthetic effect in several studies which is mainly due to its inhibitory effects towards Na + channels, Ca 2+ channels, and glutamate receptors (AMPA type) effectively suppressing symptoms of chronic, inflammatory, and neuropathic pain in vivo (Jarvis et al, 2007;Weiser, 2008).…”
Section: Current Medicational Options For Gdmentioning
confidence: 99%